2021
DOI: 10.1016/j.ajogmf.2021.100376
|View full text |Cite
|
Sign up to set email alerts
|

Defining the risk profile of women with stage 1 hypertension: a time to event analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…31 We created plots of SBP and DBP (x-axis) and individual predicted risks of preterm delivery with 95% confidence intervals (y-axis) (Figure S1). We estimated associations between ACC/AHA BP categories and risk of preterm delivery stratified by maternal age (<30 years vs. ≥30 years, cut-offs decided a priori) to improve comparability with other US cohorts 19,22,24,32,33 that have included samples of women younger than those included in our sample. We hypothesised that effect measure modification by maternal age may help explain heterogeneity in findings across studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 We created plots of SBP and DBP (x-axis) and individual predicted risks of preterm delivery with 95% confidence intervals (y-axis) (Figure S1). We estimated associations between ACC/AHA BP categories and risk of preterm delivery stratified by maternal age (<30 years vs. ≥30 years, cut-offs decided a priori) to improve comparability with other US cohorts 19,22,24,32,33 that have included samples of women younger than those included in our sample. We hypothesised that effect measure modification by maternal age may help explain heterogeneity in findings across studies.…”
Section: Discussionmentioning
confidence: 99%
“…6,12,17 The epidemiologic studies that have examined pre-pregnancy blood pressure in this range report mixed results, with risk estimates for the association between stage I hypertension and preterm delivery ranging from 1.05 to 3.8. [18][19][20][21][22][23][24][25][26] More research is needed to inform clinical decision making for this group.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Of 52 articles selected for full-text review, further exclusions (including removal of duplicate publications 28 ) left 23 studies that reported on the association between ACC-AHA BP categories based on BP measurements before 20 weeks gestation and adverse pregnancy outcomes. 8 , 9 , 10 , 11 , 13 , 14 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 …”
Section: Resultsmentioning
confidence: 99%
“…Overall, 16 studies reported adjustment for maternal covariates, most commonly maternal age, prepregnancy BMI, parity, and/or race and ethnicity 8 , 9 , 10 , 11 , 14 , 30 , 31 , 33 , 35 , 36 , 37 , 38 , 42 , 43 , 44 , 46 ; 7 of these studies reported both adjusted and unadjusted analyses. 8 , 9 , 31 , 42 , 43 , 46 , 47 In all analyses, adjustment for maternal confounders reduced the association between BP categories and adverse outcomes, most significantly for stage 2 hypertension when reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation